2016
DOI: 10.5194/isprs-archives-xli-b2-567-2016
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-Temporal Analysis of Social Media Data Related to Nepal Earthquake 2015

Abstract: Social Medias these days have become the instant communication platform to share anything; from personal feelings to the matter of public concern, these are the easiest and aphoristic way to deliver information among the mass. With the development of Web 2.0 technologies, more and more emphasis has been given to user input in the web; the concept of Geoweb is being visualized and in the recent years, social media like Twitter, Flicker are among the popular Location Based Social Medias with locational functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Table 2 was created by the authors based on Thapa [ 36 ] and Pena [ 37 ] to show the most used hashtags when earthquakes were produced in different parts of the world. In the case of the Mexican earthquake, the hashtags #sismo and #FuerzaMexico were the most frequently used, highlighting thus the trending topics in that country throughout the year 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 was created by the authors based on Thapa [ 36 ] and Pena [ 37 ] to show the most used hashtags when earthquakes were produced in different parts of the world. In the case of the Mexican earthquake, the hashtags #sismo and #FuerzaMexico were the most frequently used, highlighting thus the trending topics in that country throughout the year 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the earthquake that hit Haiti in 2010 and shocked the world, #Haiti was the most shared hashtag throughout the world during that year. Furthermore, with respect to the earthquake in Nepal, during the month following the catastrophe, 33,610 tweets were published with the hashtag #nepalearthquake [ 36 ]. These figures show how the comments are grouped with respect to a topic around a series of hashtags shared by other users and can be studied to obtain information [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Field investigation revealed disaster information needs in detail, but the timeliness and regional range of acquiring disaster information were limited [ 82 ]. Future methods of acquiring data may consider combining field investigation with big data mining, such as using data extracted from social media [ 24 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ], Google Trends [ 92 , 93 ], and Baidu Index [ 94 , 95 ]. In particular, these several data sources can make it possible to quite easily track the behavior of Internet users in real time.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have focused on Twitter, mobile applications and crowdsourced mapping both during the disaster response and recovery phase. Thapa (2016) analysed location‐based tweets posted during the 2015 Nepal earthquake to understand the spatial and temporal characteristics of the tweets. The study concluded that a relatively small number (22%) of people used hashtags related to the event, whereas most of the tweets were without any hashtag.…”
Section: Related Workmentioning
confidence: 99%